2011
DOI: 10.17305/bjbms.2011.2628
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemoradiotherapy on vaginal and sexual function of patients with FIGO IIb cervical cancer

Abstract: Th e opinion regarding sexual and vaginal function of patients with advanced cervical cancer treated primarily by chemoradiotherapy has still not been formed, mainly due to inappropriate methodology as the control group was comprised of healthy women. Th e aim of this study is to, by means of interview, evaluate vaginal and sexual function of patients with advanced cervical cancer before and after chemoradiotherapy and compare the results. A number of  patients were irradiated by teleradiotherapy dose of  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Three studies reported QoL assessments that were specific to age ( Table 2 ). 21 22 26 Conway et al 21 noted that more problems were encountered by older patients compared with younger patients, signifying that age may be an important determinant of both distress and overall QoL. Furthermore, Nunes de Arruda et al 22 noted that age affected scores on body image, sexual activity, and menopausal symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies reported QoL assessments that were specific to age ( Table 2 ). 21 22 26 Conway et al 21 noted that more problems were encountered by older patients compared with younger patients, signifying that age may be an important determinant of both distress and overall QoL. Furthermore, Nunes de Arruda et al 22 noted that age affected scores on body image, sexual activity, and menopausal symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…37 In our review, the EORTC QLQ-C30 and CX24 were the most commonly used tools in evaluating health-related and disease-specific QoL. 19,22,23,[25][26][27] Two papers characterized the temporal evolution of health-related QoL among LACC survivors. 19,21 One reported improvement at 12, 24, and 36 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following radical hysterectomy for locally advanced cervical cancer, there was no significant difference in sexual activity and enjoyment between women with benign or malignant disease; however, the cancer group had worse problems than healthy controls with body image and vaginal functioning [15]. In women with advanced cervical cancer given chemoradiotherapy, pain during intercourse was in fact reduced after treatment [16]. This may have been a result of the resolution of bleeding, discharge, and pelvic pain.…”
Section: Sexual Difficulties Arising From Symptoms and Treatments Formentioning
confidence: 98%